Modeling and control of a 3-DOF articulated robotic manipulator using self-tuning fuzzy sliding mode controller. Issue 1 (1st January 2021) - Ashagrie, Aderajew; Salau, Ayodeji Olalekan; Weldcherkos, Tilahun
Abstract: Robotic manipulators are highly coupled multi-input multi-output (MIMO) nonlinear systems with uncertainties and highly time-varying dynamic capabilities. These characteristics make the trajectory control of a robotic manipulator very challenging. This paper presents the modeling and trajectory tracking control of a 3-DOF robotic manipulator using self-tuning fuzzy sliding mode controller (ST-FSMC). The stability of the system was investigated using the Lyapunov direct method. The controller was implemented using MATLAB/Simulink and its performance was evaluated. The simulation results show that the proposed controller removed chattering phenomena from the control effort and reduced the tracking error (average steady-state error) to 0.0036 rad. However, in the case of the conventional controllers, the average steady-state e rror increased to 0.0413 rad, 0.0044 rad, and 0.0053 rad for the Proportional-integral-derivative (PID) controller, Sliding mode controller (SMC), and Fuzzy sliding mode controller (FSMC), respectively. The conventional controllers (PID, SMC, and FSMC) were designed for the purpose of comparison with the proposed ST-FSMC. The simulation results show that the designed controller (ST-FSMC) has a superior tracking performance, is robust and is not sensitive to applied model parameter variations as compared to other conventional controllers.